Participation in Multiple Policy Venues in Governance of Chile S Santiago Metropolitan Region: When Institutional Attributes Can Make the Difference - Arias-Yurisch, K (John Wiley and Sons Inc, 2024)
The complexity of metropolitan polycentric governance is still challenging scholars and practitioners, who have mostly been engaged in a normative debate in which scant attention has been paid to the coexistence and interdependence of institutional solutions. The ecology of games framework (EGF) can be used to remedy this gap. By incorporating the analysis of institutional variation into EGF propositions about venues interdependence, this article examines the mechanisms of metropolitan governance configuration resulting from institutional complexity at the inter-municipal level. Provincial forums, municipal associations, and inter-municipal agreements are the policy venues studied in the Santiago Metropolitan Region, Chile. Official documents reporting formal agreements in 2017–2021 help to capture the inter-municipal governance network to which we apply exponential random graph models (ERGMs). The results show the positive effects of mandated provincial venues on inter-municipal ties and the absence of the effect of self-organized municipal associations, tendencies that prevail even when incorporating other relevant covariates into the models. These results nourish the EGF debate about interdependencies between coexisting policy venues, emphasizing the role of the different institutional attributes framing the policy venues and the effects of these differences on governance formation. © 2024 Policy Studies Organization.